Which factors are influencing artistic swimming performance? - Ntomali, S.; Adamakis, M.; Venetsanou, F.; Chairopoulou, C.; Psychountaki, M. (European Journal of Physical Education and Sport Science, 2021)
Rhythmic ability (RA) plays an important role in sports in which music accompaniment is used, such as artistic swimming (AS). The aim of the present study was to investigate RA's relationship with the athletes` overall performance in AS, as well as the independent scores of AS performance (i.e., Execution, Artistic Impression and Difficulty), taking into account their competitive category and experience. The sample consisted of 47 female artistic swimmers (age 15.8±3.3 years; athletic experience 6.6±3.3 years) divided into three competitive categories (Senior, Junior, and Comen). The High/Scope Rhythmic Competence Analysis Test (Weikart, 1989) was used for the evaluation of RA of participants. Three official AS judges were used to assess athletes` performance in the water routine session. Descriptive and inferential (i.e., two MANCOVAs) statistical analysis revealed that experience was a significant positive predictor of AS Performance and RA, indicating that as experience increased, athletes` AS performance and RA also increased. In addition, results showed that athletes in the senior category scored higher in all variables in relation to junior and comen athletes; however, these differences were not statistically significant.